Optimization of the Pancasila student profile character through the local wisdom project of Hylocereus sp. plants - Hikamah, Siti Roudlotul; Hariyadi, Slamet; Siskawati, Fury Styo (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
The Pancasila Student Profile (PSP) character is an important element in forming an excellent and integrity-filled generation of Indonesians, because this research has only been done very little. The objective of this research should be to analyze the influence of PjBL learning on the PSP character and the dimensions of cooperation, critical thinking, and creativity through the local wisdom of the Hylocereus sp. plant. The type of research is quasi-experimental, with a two-treatment group design. The independent variable uses PjBL learning, and the dependent variable is PSP in biology learning, including practical training in making Bokashi and maintaining dragon fruit plants. The population in this study was students of SMP Negeri 2 Pesanggaran, Banyuwangi Regency, East Java, Indonesia. The research sample consists of students undertaking a local wisdom project, 30 students in group A and 30 students in group B, for a total of 60 people. Instrument research is an observation sheet of the PSP character adapted from the Ministry of Education and Culture of the Republic of Indonesia. The data obtained were analyzed using multivariate analysis, namely MANOVA. The research results indicate a simultaneous effect of the PjBL learning model on the PSP character and a partial effect on the dimensions of cooperation, critical thinking, and creativity (sig < 0.05). Thus, local wisdom-based projects have proven to be an effective strategy in supporting the achievement of the PSP character and efforts for the sustainability of natural resources. Integration of local wisdom into learning can be an innovative strategy to support the sustainability of natural resources while forming students with integrity by Pancasila values.